Peran Pendidikan Berbasis Kearifan Lokal di Pondok Pesantren Kauman Lasem dalam Meningkatkan Nilai-Nilai Islam, Kerukunan, dan Toleransi - Sunaji, Sunaji (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This study examines the role of local wisdom-based education at the Kauman Lasem Islamic Boarding School (Chinese community) in improving Islamic values, harmony, and tolerance in the Rembang community. The object of this study is the Islamic boarding school community that blends with the local Chinese community. The purpose of this study is to understand how the local wisdom approach is able to harmonize interfaith relations and encourage social integration in a multicultural environment. The method used is qualitative descriptive, with data collection through interviews, observations, and documentation studies. The results of the study indicate that education that combines Islamic values with local culture has succeeded in creating a strong atmosphere of tolerance between Muslims and the Chinese community. The discussion focuses on the efforts of Islamic boarding schools in integrating local culture with Islamic teachings, which not only strengthen spiritual values, but also strengthen social harmony. In conclusion, local wisdom-based education at the Kauman Lasem Islamic Boarding School is able to improve harmony and tolerance in the Rembang community. Keywords: Education, Local Wisdom, Islamic Values, Harmony, and Tolerance